Tissue Processor Based PLC (Programmable Logic Controller) - Ferdianita Neny; Her Gumiwang Ariswati; Tri Bowo Indrato (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2019)
Tissue Processor Tissue Processor consists of consists of several stages of dehydration, clearing, and paraffin infiltration.Phase dehydration to remove water content in tissues by immersion into alcohol. Clearing stage is the process of pulling out the alcohol content in the network by using a liquid xylol. Paraffin infiltration stages is the stage of filling cavities with liquid paraffin tissue. The purpose of this research is to modify the equipment that had broken before became an useful equipment that use basic controlled PLC. This modification tool-making using the